A Disconcerting Sarcoidosis, When The Spine Gets Involved... - Selma Abdellaoui; Kamal Allal (Swiss Journal of Radiology and Nuclear Medicine)
Bone involvement in sarcoidosis is uncommon and may be discovered incidentally when pain appears in affected patients. Indeed, the pelvic-spinal location is the most widespread: It can manifest when spine is affected by inflammatory pain, sometimes mimicking authentic spondylarthritis in certain cases, and may even suggest a malignant lesion by its radiological appearance. We describe the original observation of a patient suffering from inflammatory and insomnia-causing spinal pain in whom  the diagnosis of mediastinal sarcoidosis was retained in therapeutic abstention on the pulmonary level. Observation: 52-year-old female patient who had presented for barely a year a chronic cough accompanied by basithoracic pain, leading her to perform a chest CT scan which found bilateral medistinal-hilar adenopathies and peri-lymphatic pulmonary nodules. The diagnosis of type2 sarcoidosis was immediately considered. The additional investigations have indeed confirmed the suspected disease on the clinical and radiological level, in particular y converse enzyme positivity, the tuberculin anergy on the IDR, the lymphocyte predominance in the bronchoalveolar fluid but more particularly by he demonstration of the epithelial-giant cellular granuloma on the right iliac lymph node biopsy. However, the patient presents with inflammatory back pain, sometimes causing insomnia. A spinal MRI showed nodular bone marrow replacement lesions with pronounced T1 hyposignal and T2 hypersignal enhanced after gadolinium injection. Fortunately, she does not present bone fractures and no osteoporosis on bone densitometry. Conclusion: Faced with spinal symptoms in a context of sarcoidosis, bone involvement must be considered, espacially since there is no correlation between the clinical picture and imaging. The latter most often  has a favorable prognosis in the absence of fractures despite sometimes suspicious imaging. The case of our patient clearly illustrates the bone-related nature of the disease; back pain can be particularly intense and should lead to discussion of the use of corticisteroids or even basic treatment for rheumatic diseases.